Effect of psychological and institutional factors on student's entrepreneurial intention: an application of TPB, CSE and TT - Bularafa, Bukar Ali; Abdullah, Abdul Rashid (Universiti Putra Malaysia Press, 2019)
Unemployment and poverty are seriously issue of concern globally, especially in developing countries like Nigeria. Unemployment and poverty among university graduates in Nigeria, the trends on rising every year, major corporations are cutting down jobs and graduates who were interested to work can’t seem to find a job. However, entrepreneurship and business formation have been recognised around the World as a remedy for unemployment and pivotal for economies to grow. Therefore, promotion of entrepreneurial activity becomes the most top priority on the government agenda. Despite the unique role played by entrepreneurship to the economy as a whole and to the person that established business, in Nigeria, the rate of university graduates in entrepreneurship is far below expected. This led to many research efforts on factors that are having an effect on student’s entrepreneurial intentions. This review paper proposed the intention to be an entrepreneur can be explained by Ajzen, (1991) theory of planned behaviour, institutional, and core self-evaluation theories. Psychological (self-efficacy, risk-taking propensity, locus of control, innovativeness, need for achievement) and institutional (university environment, government support programmes) factors will have an effect on attitudes, subjective norms, perceived behavioural control. Consequently, the study predicted the entrepreneurial intentions of the Nigerian university students.